Clinical and pathological correlations of marrow PUMA and P53 expressions in myelodysplastic syndromes. Issue 5 (4th April 2015) - Bektas, Ozlen; Uner, Aysegul; Buyukasik, Yahya; Uz, Burak; Bozkurt, Sureyya; Eliacik, Eylem; Işik, Ayse; Haznedaroglu, Ibrahim Celalettin; Goker, Hakan; Demiroglu, Haluk; Aksu, Salih; Ozcebe, Osman Ilhami; et al.
Abstract : p53 is a key regulator of apoptosis. p53 upregulated modulator of apoptosis (PUMA) is a critical mediator of p53‐dependent and independent apoptosis. The objective of this study was to evaluate the relationship of p53 and PUMA to the prognosis of MDS. Bone marrow biopsies of MDS patients at the time of diagnosis (n = 76) and at the time of transformation (n = 19) were included in the study group. The expression of p53 and PUMA was evaluated using immunohistochemistry. When compared to the control group, both p53 (p < 0.001) and PUMA (p = 0.012) expression levels were significantly higher in MDS group. In MDS group, there was a moderate positive correlation between p53 and PUMA expressions. PUMA expression was not correlated with event free and overall survival. However, overall survival was significantly lower in cases with p53 expression in more than 50% of the cells. There was an increase in PUMA expression in cases that showed transformation as compared to the initial diagnostic bone marrows but was not statistically significant. The correlation that existed between p53 and PUMA was lost in transformed cases. Our results showed that PUMA and p53 expressions are increased in MDS marrows compared to normal marrows. PUMA expression increases further during transformation while the expression of p53 is not significantly altered which suggests that PUMA alterations might be a late event during the evolution of MDS.